Dual-mode frequency multiplier in graphene-base hot electron transistor. Issue 6 (24th January 2023) - Liang, Bor-Wei; Li, Min-Fang; Lin, Hung-Yu; Li, Kai-Shin; Chen, Jyun-Hong; Shieh, Jia-Min; Wu, Chien-Ting; Simbulan, Kristan Bryan; Su, Ching-Yuan; Kuan, Chieh-Hsiung; Lan, Yann-Wen
Abstract : A graphene-base hot electron transistor integrated with a 2D material heterojunction is demonstrated as a frequency modulator. Our device can operate as a doubler or tripler with AC signals from 100 kHz to 10 MHz in single tunneling transistor. Abstract : Since quantum computers have been gradually introduced in countries around the world, the development of the many related quantum components that can operate independently of temperature has become more important for enabling mature products with low power dissipation and high efficiency. As an alternative to studying cryo-CMOSs (complementary metal–oxide–semiconductors) to achieve this goal, quantum tunneling devices based on 2D materials can be examined instead. In this work, a vertical graphene-based quantum tunneling transistor has been used as a frequency modulator. The transistor can operate via different quantum tunneling mechanisms and generates, by applying the appropriate bias, voltage–resistance curves characteristic of variable nonlinear resistance for both base and emitter voltages. We experimentally demonstrate frequency modulation from input signals over the range of 100 kHz to 10 MHz, enabling a tunable frequency doubler or tripler in just a single transistor. This frequency multiplication with a tunneling mechanism makes the graphene-based tunneling device a promising option for frequency electronics in the emerging field of quantum technologies.